Body condition indicators: Assessing the influence of harvest location and potential thresholds for application in beluga monitoring. (September 2019) - MacMillan, Kathleen; Hoover, Carie; Iacozza, John; Peyton, Jonathan; Loseto, Lisa
Highlights: Sex-specific beluga body condition models account for size, age, location, and year. Belugas from entrapment events can serve as thresholds for body condition indicators. Spatial variability was detected and requires consideration in the use of indicators. This study aims to develop blubber thickness and girth as body condition indicators. Abstract: Monitoring marine protected areas requires simplifying complex marine ecosystems into a suite of indicators. The Tarium Niryutait Marine Protected Area (TN MPA), the first MPA in the Canadian Arctic is located in the Inuvialuit Settlement Region, NT and is selecting indicators for monitoring. Proposed health indicators for the TN MPA species of interest, the Eastern Beaufort Sea (EBS) beluga, include the body condition metrics blubber thickness and girth. Sex-specific body condition models for both metrics were developed to account for age, size, location, and timing of harvest from belugas harvested from 2000 to 2015. Models were tested to determine if the spatial variation is detected in the condition of belugas between the three areas of the TN MPA and between belugas harvested inside to outside of the TN MPA. Lastly, we assessed belugas from entrapment events to determine if indicator thresholds could be developed. Three of the indicators (girth male, girth female, blubber thickness male) contain both temporal and spatial factors, signalling the significant influence of year and harvest location on condition. Male belugas harvested from the western area of the TN MPA had smaller mean blubber thickness and girth compared to the other TN MPA areas, whereas there was no significant difference in female condition across the TN MPA. There was a significant difference inside and outside the TN MPA for all four indicators, with larger mean blubber thickness inside the TN MPA, females exhibiting larger mean girth and males exhibiting smaller mean girth inside the TN MPA. Indicators confirm that belugas from entrapment events had significantly lower body condition than belugas harvested during the summer and can serve as thresholds for condition indicators. This study provides guidance on the selection and use of condition indicators for their application in monitoring the TN MPA and demonstrates that careful consideration is required for indicator development and selection.